Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.ajpath.2010.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Association of T-Zone Reticular Networks and Conduits with Ectopic Lymphoid Tissues in Mice and Humans

Abstract: Ectopic or tertiary lymphoid tissues (TLTs) are often induced at sites of chronic inflammation. They typically contain various hematopoietic cell types, high endothelial venules, and follicular dendritic cells; and are organized in lymph node–like structures. Although fibroblastic stromal cells may play a role in TLT induction and persistence, they have remained poorly defined. Herein, we report that TLTs arising during inflammation in mice and humans in a variety of tissues (eg, pancreas, kidney, liver, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 65 publications
7
117
0
Order By: Relevance
“…FRCs are found in inflammatory diseases in organized tertiary lymphoid tissues where there is a substantial lymphocytic infiltrate (eg, the salivary gland in Sjogren syndrome and the liver in primary biliary cirrhosis). 44 In contrast, the SSc skin fibroblast transition usually appears in lieu of major classic lymphocytic infiltrates. We postulate…”
Section: Discussionmentioning
confidence: 99%
“…FRCs are found in inflammatory diseases in organized tertiary lymphoid tissues where there is a substantial lymphocytic infiltrate (eg, the salivary gland in Sjogren syndrome and the liver in primary biliary cirrhosis). 44 In contrast, the SSc skin fibroblast transition usually appears in lieu of major classic lymphocytic infiltrates. We postulate…”
Section: Discussionmentioning
confidence: 99%
“…TLOs are characterized by their cellular, organizational, chemokine, and vascular similarity to SLOs, especially LNs. These similarities include T and B cell compartmentalization, APCs such as DCs and follicular DCs, stromal cells (5), conduits, and a highly organized vascular system of HEVs and LVs (see below) (5,22,23). Common features of TLOs and LNs are depicted in Figure 1.…”
Section: Tlosmentioning
confidence: 99%
“…In secondary lymphoid organs, such as LNs, CXCL13 is expressed by stromal cells and Th cells in GC, with its ectopic expression promoting lymphoid neogenesis (40). A comparison of CXCL13 expression with other cytokines/chemokines in an extensively and a minimally infiltrated tumor ( Figure 7C) showed that the majority were expressed by infiltrating leukocytes (CD14 + monocytes, CD4 + T cells, or the remaining mixture of CD45 + cells) but not the EpCAM + epithelial/tumor cells.…”
Section: Figurementioning
confidence: 99%